Association of adipokines with frailty in heart failure - Fujiki, Shinya; Watanabe, Hiroshi; Obata, Hiroaki; Suda, Masayoshi; Mitsuma , Wataru; Tomii, Asako; Sakai, Katsuyuki; Uehara, Akifumi; Shimizu, Ippei; Kashimura, Takeshi; Ozaki, Kazuyuki; Minamino, Tohru (Acta Biomedica Atenei Parmensis, 2021)
Background Frailty is a multifactorial physiological syndrome most often associated with age but which has received increasing recognition as a component of chronic illnesses such as heart failure. Patients with heart failure are likely to be frail, irrespective of their age. Adipokine dysregulation, which is associated with frailty, occurs in patients with heart failure. In this study, we tested the hypothesis that adipokines are associated with frailty in patients with heart failure.Methods Thirty-five patients with heart failure (age, 67 ± 14 years; 25 males; left ventricular ejection fraction, 45 ± 19%) were included. Serum adipokine levels, physical performance, and body composition were measured.Results Adiponectin and leptin were inversely correlated with grip strength. Adiponectin was inversely correlated with bone mineral density. Leptin was positively correlated with fat mass. Adipokines were not correlated with skeletal muscle mass.Conclusions Adipokines were associated with frailty in patients with heart failure. Adipokine dysregulation may play a role in the development of frailty in heart failure.